Islam Between Culture and Politics - Tibi, B. author. aut Link
XVII, 271 p.
Keywords: Bassam Tibi offers a radical solution to the problems faced by Islam in a rapidly changing and globalizing world. He proposes a depoliticization of the faith and the introduction of reforms to embrace secular democracy, pluralism, civil society and individual human rights. The alternative to this is the impasse of fundamentalism. The pivotal argument is that Islam is being torn between the pressure for cultural innovation and a defensive move towards the politicization of its symbols for non-religious ends.